Fetal gender specific expression of tandem-repeat galectins in placental tissue from normally progressed human pregnancies and intrauterine growth restriction (IUGR). Issue 12 (December 2015) - Hutter, Stefan; Knabl, Julia; Andergassen, Ulrich; Mayr, Doris; Hofmann, Simone; Kuhn, Christina; Mahner, Sven; Arck, Petra; Jeschke, Udo
Abstract: Introduction: The tandem-repeat type galectins, which comprise of gal-4, -6, -8, -9, and -12, form a sub-family of galectins. Gal-6 is expressed only in rodents, whereas the other four galectins, tandem-repeat galectins, are also detectable in human tissue. The placental expression of individual members of the tandem-repeat gal family is increasingly known, however, systematic, comparative analysis especially in the human placenta from normal or pathological pregnancies is still lacking. Material and Methods: Within this study, third trimester placentas obtained at delivery (n = 14 IUGR, n = 15 controls, equally divided in placentas from male and female fetuses) were analyzed for the expression of gal-4, -8, -9 and -12 by immunohistology and immunofluorescence, data were obtained by using a semiquantitative scoring system. Double immune-fluorescence with trophoblast specific markers was used to identify co-expression in the decidua. Results: We identified dysregulation of tandem repeat galectins in IUGR placentas with a strong connection to the fetal gender. We identified a significantly lower expression of gal-4 and gal-9 in villous trophoblast tissue of IUGR placentas with male fetuses and a downregulation of gal-4 and gal-8 in extravillous trophoblast (EVT) from IUGR and male fetuses. Conversely, expression of gal-9 and gal-12 was higher in EVT of IUGR cases in placentas with female fetuses. Double immunofluorescence using cytokeratin-7 confirmed the expression of tandem-repeat galectins in EVT. Discussion and Conclusion: The human placenta expresses tandem-repeat type galectins in villous trophoblasts, EVT, endothelial cells and decidual stromal cells. Summarizing all effects, there is significant down-regulation of gal-4, -8 and gal-9 in the IUGR trophoblast of male fetuses. In contrast, in IUGR pregnancies with female fetus gal-9 and gal-12 are upregulated in the EVT and in endothelial cells in the cases of gal-12. Therefore we propose a fetal-gender specific action of tandem repeat galectins in IUGR placentas. Highlights: We identified dysregulation of tandem repeat gals related to the fetal gender. Gal-4, -9, 12 are downregulated in IUGR placentas with male gender. Gal-9 and -12 are upregulated in IUGR EVT with female fetal gender. Gal-4 is downregulated in decidual stromal cells in IUGR with male gender. Gal-12 is upregulated in endothelial tissue in IUGR with female gender.